2009
DOI: 10.1016/j.acvd.2009.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and management of smoking-cessation strategies among cardiologists in France: A nationwide survey

Abstract: French cardiologists are rarely involved in the management of smoking cessation. Their own smoking status influences their attitudes towards the management of smoking cessation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
1
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 12 publications
1
14
1
3
Order By: Relevance
“…regarding smoking-cessation support [44 ]. Of note, 8% of the respondents declared themselves as active smokers, significantly lower than the 27% reported in 1993 in the same country [45], but higher than rates reported in the US (1.3%) and in the Netherlands (4.3%) [46,47].…”
Section: Abdominal Aorta Aneurysmcontrasting
confidence: 55%
See 2 more Smart Citations
“…regarding smoking-cessation support [44 ]. Of note, 8% of the respondents declared themselves as active smokers, significantly lower than the 27% reported in 1993 in the same country [45], but higher than rates reported in the US (1.3%) and in the Netherlands (4.3%) [46,47].…”
Section: Abdominal Aorta Aneurysmcontrasting
confidence: 55%
“…Importantly, nonsmoking and past-smoking cardiologists were significantly more committed to check smoking status and provide assistance than their smoking counterparts [44 ]. These data are confirmed by a recent international survey on family physicians: fewer smoker than nonsmoker physicians volunteered that smoking was a harmful activity (64 vs. 77%; P < 0.001) and discussed smoking at every visit (34 vs. 45%; P < 0.001) [48].…”
Section: Abdominal Aorta Aneurysmsupporting
confidence: 54%
See 1 more Smart Citation
“…One potential source both of these negative beliefs and of variations in practice are the doctors' own health behaviours. Several studies have suggested that doctors who smoke have less positive attitudes towards smoking cessation and are less likely to both take patient's smoking history and provide advice than non‐smoking colleagues . However, the extent to which personal smoking behaviour affects the physician's clinical practice is an important public health issue that has not been comprehensively investigated.…”
Section: Introductionmentioning
confidence: 99%
“…That health professionals' own health and health habits may influence their attitudes towards relevant professional behaviours has been demonstrated by many studies of cigarette smoking and physical exercise. Health professionals who smoke have less favourable attitudes towards smoking cessation (9)(10)(11)(12)(13)(14)(15)(16)(17)(18), less confidence in their efficacy to help the patients to quit smoking (6,(19)(20)(21)(22)(23)(24)(25)(26) and less intention to counsel their patients (19,27,28), and are less likely to perceive themselves as role models for their patients or the general population (13,(29)(30)(31)(32)(33)(34)(35)(36), when compared with non-smoking health professionals. Similar findings have been reported with respect to physical activity with unfit health professionals being less likely to hold positive attitudes towards promoting physical activity than physically fit health professionals (37)(38)(39)(40)(41).…”
Section: Introductionmentioning
confidence: 99%